Reflections of Egress Students about a Graduate Course in “Letras”/English - Carvalho, Eliana Márcia dos Santos (The ESPecialist, 2014)
This work aims at knowing the conceptions about an Undergraduate English course in Bahia and it is justified by the necessity to understand the reasons why the majority of undergraduates resist to work as teachers when they finish the course. This is a case study that follows the qualitative approach. This research is about the six teachers’ perceptions, regarding the Undergraduate course they took: English, Portuguese and their respective Literatures. The research objectives are: to understand the reasons why graduates resist working as teachers and to investigate the conceptions about the teacher education and the area of activity of teachers who took “Letras” course – specialization in Portuguese, English and Literatures. The theoretical bases used were the LDB 9394/96 (BRASIL, 1996), the PCN – Foreign Language (BRASIL, 1998), Celani (2000, 2004), Almeida Filho (1999) and Freire (1996).